Aplikasi Materi Seni Rupa Kolase Bahan Sampah Organik Di Kelas IVC SDN 52 Kota Bengkulu - Utami, Inka; Parmadi, Bambang (Universitas Bengkulu, 2025)
This study aims to describe the process of making and forming collages from organic waste in the school environment as a result of applying fine art materials in class IV C State Elementary School 52 Bengkulu City. The research uses a descriptive qualitative approach with class teachers and grade IV C students as subjects. The researcher served as the main instrument supported by observation, interview, and documentation guidelines. Data analysis was conducted through data collection, condensation, presentation, and conclusion drawing. Techniques used were observation, interviews, documentation, and data validity checks through triangulation and member check. The results show that: (1) The collage-making process begins with preparation, namely collecting and selecting materials such as dry leaves and tree branches, and preparing cardboard as a base. Tools used include scissors and white glue. The implementation stage involves cutting dry leaves, arranging temporary patterns, gluing, and finishing according to students’ creativity. (2) The forms of collage works produced are guided by elements of art such as point, line, plane, shape, color, texture, and light–dark, along with principles of unity, balance, rhythm, and harmony. In conclusion, the collage-making process using organic waste was successfully carried out by students. The resulting works demonstrate creativity and application of art concepts, producing five distinct forms of collages described according to artistic elements and principles. This activity not only fosters creativity but also introduces environmentally friendly practices in art learning.